Halal industry as Indonesia’s new economic engine: The role of Mutual Recognition Agreements - Manthovani, Evita; Afandi, Frendy Ahmad; Susyanti, Susi; Indrasti, Dias; Indriyani, Lili; Permatasari, Gita; Khankasikam, Nichanan (Halal Studies and Society, 2025)
The acceleration of halal certification is a strategic policy issue in the global Islamic economy during the rise of cross-border demand for halal products. Only 28.8% of food and beverage enterprises in Indonesia had obtained halal certification as of February 11, 2025, despite the country’s strategic position in the global market. Therefore, this study aims to examine the role of Mutual Recognition Agreements (MRA) in facilitating halal certification with a particular focus on food and beverage products through regulatory harmonization. MRA documents and international halal regulatory frameworks are analysed using an empirical qualitative method, supported by semi-structured interviews with halal certification stakeholders. The results suggest that MRA is expected to streamline procedures, avoid duplication, and improve efficiency, particularly in cross-border certification. However, the effectiveness is constrained by differences in Sharia interpretation, uneven testing infrastructure, and coordination challenges. MRA can support more efficient halal certification when reinforced by institutional capacity building and digitalized certification systems.